Corporate networks, corporate governance and directors remuneration - Abdul Rahman, Rashidah; Wan Abdullah, Wan Mohammad Taufik; Quigley, Behnaz Z. (2012)
This study endeavour to examine the association between social networks and executive and non-executive directors' remuneration on the financial and non-financial industry. More specifically, this study analyses how the social network elements; independent directors, non-independent directors, executive directors, interlock boards, political connection and directors' prestige could influence the directors; remuneration determination. Malaysia provides a suitable setting to examine the relation between the social networks and directors' remuneration since it exhibits the scenario of politically connected firms due to their diverse ethnic ownership compared to similar firms in capital markets around the world. The study use a sample of 221 companies for a five-year period from 2006-2010. The results reveal that the main contribution to the level of total directors' remuneration comes from the short-term pay rather than the long-term pay package. Besides, it is found that the non-independent directors, executive directors, political connection and directors' prestige are significantly associated with the short term pay. The study also found that the non-independent directors, independent directors, executive directors, and directors' prestige are associated with the long-term pay. Lastly, there is a significant relationship between non-independent directors, non-executive directors, executive directors, political connections, and directors' prestige with the total directors' remuneration.